Looking behind eye-catching design: an eye-tracking study on wine bottle design preference. Issue 1 (28th September 2020) - Merdian, Peter; Piroth, Philipp; Rueger-Muck, Edith; Raab, Gerhard
Abstract : Purpose: The purpose of this study is to find out how unconscious perception and conscious reactions differ when it comes to evaluate wine bottles in a shopping shelf. It was evaluated how attention is related to subjective evaluations of interest and value in the perception of wine bottle design choices. Design/methodology/approach: The experiment combined implicit eye-tracking observations and a quantitative measurement on the assessment on wine bottle designs. In total, 37 participants rated eight different wine bottle designs based on their interest and assumed value, without any given information about the wines' original price classification. Findings: There is a significant difference between the perception of wine bottle designs. Eye-catchy designs do not automatically transform into a higher perception of value and interest towards the product. The unconscious perception of bottles and the conscious reaction differentiate. Research limitations/implications: The greatest limitation, as with many other implicit studies, is the limited number of subjects and the associated limited validity. In addition, eight bottles in four categories were studied, which is adequate, but does not fully reflect the complexity of the wine market supply. Practical implications: Manufacturers and wine label designers should challenge existing pre-disposition towards certain wine bottle design choices. Originality/value: To the best of the authors' knowledge, this is the first German consumer study that focusses on unconscious perception (measured by implicit eye movement behaviour) and conscious reactions in the context of explicit value and interest evaluation.